ON \beta-ABSORBING PRIMARY SUBMODULES - Thawatchai Khumprapussorn (International Journal of Apllied Mathematics, 2024)
In this paper, we define the notion of -absorbing primary submodules.We can see that -absorbing primary submodules are a generalization of absorbing submodules and 2-absorbing submodules.Several properties concerning -absorbing primary submodules and examples are given. MSC 2020
Keywords: Fuzzy and Soft Set Theory